CARE FOR DRUG USERS IN A FAMILY HEALTH STRATEGY: POTENTIALS AND CHALLENGES - Silva, Vanessa Alvez Mora da; Pinho, Leandro Barbosa de; Nasi, Cintia; Siniak, Débora Schlotefeldt; Santos, Elitiele Ortiz dos; Ávila, Marciele Barcelos; Palskuski, Kauana Lima (Cogitare Enfermagem, 2024)
Objective: To assess the potential and challenges in caring for users of psychoactive substances in a Family Health Strategy through the perception of professionals. Method: A qualitative case study was carried out using the Fourth Generation Evaluation, developed in 2023, in a Family Health Strategy in a municipality in Rio Grande do Sul, Brazil, with 19 professionals. Previous ethnographic techniques were used, interviews were conducted using the hermeneutic-dialectic circle, and the constant comparative method was used to analyze the data. Results: Team commitment and matrix support are potentialities. The challenges are difficulties establishing bonds with users, fears, and stigmas, the team's lack of preparation, and the lack of physical structure and professionals. Conclusion: This study has helped to uncover the challenges encountered in caring for drug users and aims to promote care that embraces and integrates the individual.